The Palgrave Handbook of the European Administrative System - Bauer, M.; Trondal, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Drawing on research from the administrative sciences and using organizational, institutional and decision-making theories, this volume examines the emerging bureaucratic framework of the EU and highlights that analyzing the patterns and dynamics of the EU's administrative capacities is essential to understand how it shapes European public policy.
Keywords: Public policy; European Union; Political theory; Political science; Public administration; Public Policy; European Union Politics; Political Theory; Political Science; Public Administration